Antioxidant Activity and Phenolic and Flavonoid Contents of the Extract and Subfractions of Euphorbia splendida Mobayen - Zahra Kefayati; Saeed Mohammadi Motamed; Asie Shojaii; Mitra Noorix; Mitra Noori; Roshanak Ghods (Pharmacognosy Research, 2017)
Introduction: The harmful action of the free radicals which cause the oxidative stress can be blocked by antioxidant substances, and different plant extracts showed antioxidant activity. The aim of this study is was evaluation the antioxidant activity of total methanol extract (ME) and subfractions of Euphorbia splendida Mobayen. Materials and Methods: Aerial part of E. splendida was extracted by maceration with methanol and then subfractionated by liquid–liquid fractionation using petroleum ether, chloroform, ethyl acetate, and water. Antioxidant activity was assessed by 2,2‑diphenyl‑1‑picrylhydrazyl (DPPH) radical scavenging activity assay, reduction of ferric ions and ferrous ion chelating potential. Total phenolic contents (TPC) and total flavonoid contents (TFC) were estimated with Folin‑Ciocaltue and aluminum chloride methods, respectively. Results: The findings revealed that E. splendida ME and subfractions showed a dose‑dependent antioxidant activity. ME showed the highest antioxidant activity based on total reduction capability and ferrous ions chelating assay tests. Aqueous fraction and then ethyl acetate fraction showed the best IC50 in DPPH radical scavenging test in comparison to butylated hydroxytoluene. ME showed the highest value of TPC and TFC (270.74 ± 0.005 mg/g and 208.23 ± 0.007 mg/g, respectively). Conclusion: This study showed that the extract and subfractions of E. splendida have antioxidant activity. The antioxidant activity of the extract and fractions might be attributed to the presence of phenolic compounds. More studies are needed to determine the active antioxidant compounds of this plant.
Keywords: 1; 1‑Diphenyl‑1‑picrylhydrazyl; Antioxidant; Euphorbia splendida; Flavonoid; Fractions; Free radicals